When the Empire calls : patriotic organisations in New Zealand during the Great War : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Hucker, Graham (Massey University, 1979)
One noticeable feature of theses completed in New Zealand in recent years has been the absence of studies dealing explicitly with aspects of the Great War. Some thesis writers have used the War years as convenient departura and initiation points for their particular topics of study. Others have spanned the war years using a wider chrohological context with the result that a limited number of studies have been presented on the watershed years 1914 to 1918. Upon researching this topic, maps were constructed to plot the location of patriotic organisations and kindred bodies active during the War in an attempt to achieve some sort of illustrative perspective. The ensuing result virtually left no corner of New Zealand untouched. The situation is quite different today however. At present there exist fourteen provincial patriotic councils which focus primarily on the Second world War. The only exception being the Otago Provincial Patriotic Council which has retained files covering the Great War. These files have recently passed into the possession of the Hocken Library
Keywords: World War, 1914-1918; World War I; First World War; Patriotism; Patriotic societies; New Zealand; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History